Հայ-իրանական ռազմական գործակցութիւնը 1720 -30ականներին - Ղազարեան, Գոռ; Նազարեան, Հայկ (տպ. Atlas)
In the early 1720s, Iran faced a deep crisis. Afghan forces captured its capital Isfahan, destabilizing the country. At the same time, Russian troops launched attacks along the Caspian coast. These events severely weakened Iran's military power and control over its territory. Iran's weakness triggered Ottoman plans to invade Transcaucasia. Their goal was to occupy the region and move deeper into Iran. The Armenian provinces of Syunik and Artsakh had strong defensive positions. Their local rulers (the melik s) had considerable fighting forces. In 1727, Davit Bek (the leader of Syunik) signed a military agreement with Iran's Shah Tahmasp II. This created a formal alliance against the Ottomans. In the 1730s, Nader Khan (who later became Nader Shah) led Iran's forces. He worked closely with Armenian military leaders. Armenian troops joined the Iranian army against the Ottoman army. The most important battle took place at Yeghevard in 1735. Armenian and Iranian forces won a major victory there, which forced the Ott omans to retreat from Transcaucasia.
Keywords: Պատմութիւն; Հայ-իրանական հարաբերութիւններ